Крушение иллюзий: роман / Владимир Шитов - Шитов Владимир Кузьмич (Спецсериал "Сыщики", 2002)
Экземпляры: Аб (20140807) / Инвентарный номер: 101441 / Цена: 50.00 / Авт.знак: Ш 64 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6